2008
DOI: 10.1587/elex.5.120
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth of vanadium-doped ZnSe using triethoxyvanadyl by metal-organic vapor phase epitaxy

Abstract: Abstract:As a new diluted magnetic semiconductor, vanadiumdoped ZnSe is theoretically predicted to induce ferromagnetism above room temperature without carrier doping. Vanadium-doped ZnSe was epitaxially grown on (100) GaAs substrate by metal-organic vapor phase epitaxial method in an atmospheric pressure. As a dopant source of vanadium, triethoxyvanadyl was used. The influences of molar supply ratio of dimethylzinc to dimethylselenide on crystallinity were investigated in order to research the optimum vanadiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In previous studies, we reported that the crystal growth condition of ZnSe was changed from epitaxial growth to polycrystal growth at a VI/II ratio between 1.2 and 1.5, as determined from the results of structural analysis using X-ray diffractometry with a 2-scan. 18,19) In other words, this region where the VI/II ratio is between 1.2 and 1.5 corresponds to the transition region, which is divided into the epitaxial and polycrystal growth regions. The limit of vanadium concentration that could maintain the epitaxial growth condition was considered to be about 0.2%.…”
Section: Effects Of Vanadium Doping On Crystal Structure Of Znsementioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we reported that the crystal growth condition of ZnSe was changed from epitaxial growth to polycrystal growth at a VI/II ratio between 1.2 and 1.5, as determined from the results of structural analysis using X-ray diffractometry with a 2-scan. 18,19) In other words, this region where the VI/II ratio is between 1.2 and 1.5 corresponds to the transition region, which is divided into the epitaxial and polycrystal growth regions. The limit of vanadium concentration that could maintain the epitaxial growth condition was considered to be about 0.2%.…”
Section: Effects Of Vanadium Doping On Crystal Structure Of Znsementioning
confidence: 99%
“…More specifically, the molar supply ratio of DMSe to DMZn (VI/II ratio) was set to 1.2, which is the epitaxial growth condition. 18,19) The supply rate of TEV was maintained at 0.01 mmol/min. The growth temperature was 500 C, and the growth duration was extended from 1 to 5 h. The thickness of the undoped and the vanadium-doped sample was 25 and 22 mm, respectively.…”
Section: Effects Of Vanadium Doping On Optical and Magneticmentioning
confidence: 99%